Report of Working Group on Forestry for the Ninth Five Year Plan Ministry of Environment and Forests - Planning Commission (Planning Commission, 1998)
During the first meeting of the working group held on 29.1.1996 it was decided to form sub-groups composed of members of the working group and additional coopted subject specialists to go into (i) forestry research, education and extension, (ii) forest policy, planning and management, (iii) afforestation and eco-development, (iv) resources survey and utilisation and (v) resource mobilisation. The sub-groups formed may be seen in annexure-I.
Ministry of Environment and Forests